Kajian Penggunaan Coating Atap terhadap Termal Bangunan Studi Kasus Rumah Bali Kontemporer - I Kadek Agus Darmayoga; I Putu Weka Wendyputra; Ni Made Yudantini; Try Ramadhan (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Bali is one of the tropical locations where urban heat islands are felt. An alternative that may be discussed in an effort to lessen solar heat radiation in buildings in order to improve thermal comfort without having a detrimental effect on the environment is solar reflecting paint. This study uses the Autodesk Ecotect Analysis 2011 software simulation method to demonstrate the impact of applying a layer of solar reflecting paint coating (Solar Reflectance Index = 106) on the roof of a contemporary Balinese structure. The thermal comfort of the original model and the model covered in reflective paint were compared using simulation data in the form of Mean Radiant Temperature (MRT), Predicted Mean Vote (PMV), and Predicted Percentage of Dissatisfied (PPD). A decline in the MRT, PMV, and PPD values is indicative of a change in the average thermal conditions of buildings, according to the research findings